Affiliative Leadership Styles of Female Headteachers in Public High Schools in Nepal - Acharya, Milan (Interdisciplinary Issues in Education, 2024)
This study explores the affiliative leadership styles of female head teachers in public high schools in Nepal. It aims to comprehend how subjective experiences and varied perceptions impact the leadership practiced by female headteachers through phenomenological feminist theoretical lenses. Two female headteachers were purposefully selected and interviewed for the purpose of data collection. Findings show that gender bias has a detrimental effect on female headteachers feelings of doubt about their own capacity for leadership. Nevertheless, these headteachers demonstrated resilience and accountability, which, in turn, projected their transformative potential, a change in stereotypes, and a positive impact on school governance. Affiliative leadership involves proactive and empowering strategies to promote diversity and teamwork. Also, the finding shows that female headteachers improve employee satisfaction by questioning conventional leadership norms and fostering a good culture at the workplace. By emphasizing the value of affiliative leadership in creating positive organizational cultures and improving educational outcomes, this study adds to the body of knowledge on educational leadership. It contributes to the understanding of effective leadership practices in educational contexts by referencing the insights, strategies, and contributions of female leaders in high schools in Nepal.